UJI AKTIVITAS ANTIMIKROBA EKSTRAK DIETIL ETER AKAR ANTING-ANTING (Acalypha australis L.) SECARA KLT-BIOAUTOGRAFI - A. Mumtihanah Mursyid (Fakultas Farmasi UMI, 2012)
A research had been done of antimicrobial activity of Anting-anting (Acalypha australis L.). The preliminary research was done by screening test using Staphylococcus aureus, Salmonella typhi, Streptococcus mutans, Staphylococcus epidermidis, Pseudomonas aeroginosa, Escherichia coli, Vibrio sp, Bacillus subtilis and Candida albicans toward extract of ethanol, dietyl eter and n-butanol of anting-anting (Acalypha australis L.) wich were use in 1 mg/ml. The result showed that the dietil eter extract inhibit growth of bacteria, Staphylococcus aureus, Escherichia coli, Bacillus subtilis and Salmonella typhi. The test Antimicrobial activity toward dietil eter extract of Gamal (Glyricidia sepium (Jacq).Steud.) was done by using the liquid dilution methode to find out the MIC value in concentration 0,00625%, 0,025%, 0,1%, 0,4% and 1,6% continued by spreading on solid medium to find out the MKC value. The result showed that MIC toward to Staphylococcus aureus is 0,025%, Eschericia coli is 0,1%, Bacillus subtilis is 0,025%, and Salmonella thypii is 0,025%. While MKC toward to Staphylococcus aureus is 1,6%, Escherichia coli is 0,4%, Bacillus subtilis is 0,025%, and Salmonella thypii is 0,1%. The TLC-Bioautography technique was used to predict the active constituents. The best result has been obtained from separating by means TLC which used mixture of n-hexane : ethyl acetate (3:1). The result of TLC-Bioautografi showed that the spot in Rf 0,27 and Rf 0,36 given the activity antimkrobial toward Escherchia coli, Rf 0,36 toward Bacillus subtilis, and Rf 0,45 toward Staphylococcus aureus and Salmonella typhi. The identification result of the chemical component shown that the actif compound wich given positif result as fenol on spot in Rf 0,27 and 0,36 and the active compound wich given positif result as steroid on spot in Rf 0,45.Key word : Aktivitas antimikroba, Skrining, KLT-Bioautografi, Anting-anting (Acalypha australis L.)